Kajian Kritis Terhadap Ratio Decidendi Hakim Mengabulkan Poligami Dengan Alasan Suami Hiperseksual Dari Perspektif Keadilan Gender - Fitri Hidayat (Widya Yuridika, 2020)
The Act of Marriage allows a husband to have more than one wife that can be called plural marriage (poligami in bahasa), on condition: a. the wife cannot carry out her obligations as a wife; b. the wife gets a disability or an incurable disease; c. the wife cannot give birth. The judge will give permission to the husband to marry more than one person, if they meet one of the conditions above. The ratio decidendi of these four court decisions is a concern: Putusan Nomor 0616/Pdt.G/2015/PA.Pwd, Putusan Nomor 905/Pdt.G/2012/PA.JB, Putusan Nomor 2593/Pdt.G/2017/PA.Jbg, Putusan Nomor 2670/Pdt.G/2012/PA.Lmg. This court ruling granted the hypersexual husband's request to be married more than one person. The ratio decidendi is the wife can not carry out her obligations as a wife. Hypersexual is a mental disorder. The judge granted the request by using that ratio decidendi the same as labeling the wife not do the obligation. Even though the one who has a problem is her husband. The wife has done her duty, but she is no longer able to serve because the husband is hypersexual, which actually makes the wife feel pain. The court decision leads to discrimination and also not in accordance with the principles of gender justice which is in Islam. Because Islam does not recognize discrimination. Islam recognizes the difference between men and women but is not a distinction.